Daun Sepejam adalah Mikrohabitat Sarang Tawon Kertas: Kasus Indralaya - Marisa, Hanifa (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2022)
Marisa H. 2022. Hypolytrum nemorum leaves as the nest host of pollinator paper wasp Ropalidia fasciata. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-10 Tahun 2022, Palembang 27 Oktober 2022. pp. 61-66. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Sepejam is vernacular name for Hypolytrum nemorum, a member of Ceperaceae family, but their visual leaves looks like Pandanceae. This plant usually growth at swamp side or ponds side area. Survey on 26th June, 2022 at Sriwijaya University ponds, found a sepejam plant. Study on the top leaves of this sample plant, found the paper wasp (Ropalidia fasciata) nest hanged there. Ropalidia fasciata had reported usually made their nest at sugarcane (Saccharum officinarum) and wild grass (Miscanthus sinensis) in Japan, but the nest commonly exist at Cocos nucifera in Taiwan, and often found hung at twigs and leaves of broadleaves tree in Sumatra. But now, it is found Ropalidia fasciata paper wasp, made their nest under Hypolytrum nemorum leaves, at pond side, Indralaya, Sumatra. The nest made at central vein of lining leaves, at the top of twig, close to the inflorescence. Leaves host was 15 cm length, 2 cm wide, 90 cm height from the ground surface. There are 5 individu of H nemorum clumped, and 10 inflerescences, which the pH of soil about 6.5–7 and light intensity 2000 lux at daylight, and soil humidity about 30-40 %. So, it is need to consider, protection of H nemorum in South Sumatra, as the nest habitat of pollinator paper wasp, R fasciata.